Implikasi Revisi Undang-Undang Nomor 7 Tahun 1989 tentang Peradilan Agama dan Langkah Strategis bagi Praktisi Hukum Pengadilan Agama - Syamsu Alam, Andi (Al-Mawarid Jurnal Hukum Islam, 2007)
The Act No. 3 year 2006 revising toward The Act No. 7 year 1989 concerning the religous (Islamic) court constitutes recent development after one roof system of court in Indonesia. Revising the Act No. 7 year 1989 departs from Indonesian senate proposes and initiates. This revising actually implies human resources and human assessment of the religous court in Indonesia. The Religous court faces new jurisdiction, budget, education and training effectevely, preparing syariâah graduation, law resources, experts of economics law, those of Islamic economics including the banking world and the Syariâah economics generally. Thus, it needs revitalizing the curricullum of Syariâah economics either Strata 1 or graduation program (S2) in preparing human resources and human assessment of religous court in Indonesia. Kata kunci: Peradilan agama, praktisi hukum, ekonomi Syariâah, SDM, dan kewenangan.